2011
DOI: 10.1142/s0219581x11009489
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Micron-Rubber and Nano-Silica Particles on the Fatigue Crack Growth Behavior of an Epoxy Polymer

Abstract: A thermosetting epoxy polymer was hybrid-modified by incorporating 9 wt. % of CTBN rubber micro particles and 10 wt. % of silica nano-particles. The unmodified and the hybrid-modified resins were poured into steel moulds and cured to produce bulk epoxy polymer sheets from which standard compact tension test specimens were machined. Fatigue crack growth tests were conducted using a 50 kN servo-hydraulic test machine, with following test parameters: stress ratio, R = σ min /σ max = 0.1, sinusoidal waveform and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In an earlier investigation [42] we have observed that the fatigue crack growth rate of the hybrid bulk epoxy (containing both micron-rubber and nano-silica particles) is over an order of magnitude lower than that of the neat epoxy. Further, we have observed that the use of such a hybrid matrix in GFRP enhances the constant amplitude fatigue life due to suppressed matrix cracking, delayed initiation of delamination and reduced crack / delamination growth rate [24].…”
Section: Experimental Spectrum Fatigue Lifementioning
confidence: 89%
See 2 more Smart Citations
“…In an earlier investigation [42] we have observed that the fatigue crack growth rate of the hybrid bulk epoxy (containing both micron-rubber and nano-silica particles) is over an order of magnitude lower than that of the neat epoxy. Further, we have observed that the use of such a hybrid matrix in GFRP enhances the constant amplitude fatigue life due to suppressed matrix cracking, delayed initiation of delamination and reduced crack / delamination growth rate [24].…”
Section: Experimental Spectrum Fatigue Lifementioning
confidence: 89%
“…5 clearly indicate the underlying mechanisms, i.e. suppressed matrix cracking, delayed initiation of 11 delamination, and reduced crack / delamination growth rate [42], for improved spectrum fatigue behavior in the GFRP-hybrid composite.…”
Section: Experimental Spectrum Fatigue Lifementioning
confidence: 90%
See 1 more Smart Citation
“…6. In an earlier investigation, 31 it has clearly been shown that the fatigue crack growth rate of the hybrid-modi¯ed epoxy polymer is signi¯cantly lower than that of the neat epoxy polymer.…”
Section: Fatigue Crack Growth Ratementioning
confidence: 96%
“…Small rough features are required to enhance hydrophobic character of the coating but these nano-scale structures are protected (Fig. 1) by a large, strong topography of epoxy and the combination of amine and silica nanoparticles enhances the stress resistance of the bulk material [26]. With high impact strength hydrophobic coatings usually deteriorate due to the brittle materials used, but epoxy is slightly elastic and can endure high forces before cracking or shattering which increases the overall durability and lifetime of the epoxy coating.…”
Section: Hardnessmentioning
confidence: 99%